Determination of total plasmatic proteins in birds of Ramphastos spp. by refratometry - de Almeida, Ana Laura Alves; de Oliveira, Matheus Salgado (Seven Editora, 2023)
The measurement of Total Plasma Proteins (TPP) in poultry contributes to the diagnosis of diseases such as liver failure, hemorrhages, malnutrition, anemia and infectious processes. Ramphastos spp. popularly known as toucans are birds commonly received at the Wild Animal Rehabilitation Center (CRAS) of the University of Vale do Paraíba (UNIVAP). The objective of this work was to evaluate the PPT dosage by refractometry in 10 birds of the genus Ramphastos spp. received at UNIVAP’s CRAS. Data were obtained from reports from the CRAS Clinical Analysis Laboratory (LabCRAS) and came from 16 samples. Dosage was performed using two refractometers, a manual Contec® model RZ-126 ATC and a digital Reichert® model 04232-0511 in whole blood collected with EDTAK2 anticoagulant, performed in triplicate. The data were organized using the Microsoft Office Excel® program and subsequently submitted to statistical treatment using the SISVAR software version 5.6. The analysis of the interaction between the means revealed the highest dosage in Ramphastos vitellinus with 5.95 g/dL (manual) and 9.4 g/dL (digital), followed by Ramphastos dicolorus with 5.62 g/dL (manual) and 8.0 g/dL (digital) and Ramphastos toco with 5.14 g/dL (manual) and 7.84 g/dL (digital). PPT dosage proved to be important due to the scarcity of reference values in Ramphastos spp. available in the literature. In addition, the manual method proved to be more effective. However, further studies are needed regarding the evaluation of PPT in Ramphastos spp. as well as its comparison with different analytes such as serum albumin, which represents 40 to 50% of total plasma protein in birds (normal levels range from 0.8 to 2.0 g/dL) and is synthesized in the liver. Albumin binds and transports anions, cations, fatty acids, hormones, consequently, hypoalbuminemia also affects the concentrations of these compounds. DOI: https://doi.org/10.56238/devopinterscie-014